Machine Learning Application in Analyzing Online Customer Journey - Pal, Subhabaha; Pal, Sampa (Indian Journal of Computer Science, 2019)
This is the era of internet which has given rise to multiple opportunities for online users to purchase from digital marketplaces. Understanding the consumer journey of users is important and it is also important to understand their behaviour in the online space. This is an attempt to analyze the behaviour of online users and to predict whether they will be purchasing or opting for a service based on the last touch-point they have accessed (whether it is a customer-initiated touchpoint or a company-initiated touchpoint).